PENGARUH GAYA KEPEMIMPINAN KEPALA RUANGAN, MOTIVASI DAN DISIPLIN TERHADAP KINERJA PERAWAT DI RUMAH SAKIT UMUM DAERAH (RSUD) BRIGJEND H. HASAN BASRY KANDANGAN KALIMANTAN SELATAN - Dwi Wahyu Artiningsih (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aimed to analyze the influence of leadership style of the room head nurse, motivation,discipline on the performance of nurses in hospitals Brigjend H.Hasan Basry Kandangan, analyzing variables the dominant influence on the performance of nurses in hospitals Brigjend H. Hasan Basry Kandangan. This research is explanatory research, a research that aims to get an explanation through hypothesis testing. The population in this research are all nurses who carry out their duties and functions as a nurse in the infirmary General Hospital Hospital Brigadier General H. Hasan Basry Kandangan. The research sample of 109 respondents by sampling using saturated / census and statistical analysis tools using SmartPLS (Partial Least Square). Results showed that the leadership style of the room head not significant effect on the performance of nurses in hospitals Brigjend H.Hasan Basry Kandangan motivation not significant effect on the performance of nurses in hospitals Brigjend H.Hasan Basry Kandangan, disciplined significant effect on the performance of nurses in hospitals Brigjend H. Hasan Basry Kandangan, the discipline has a dominant influence on the performance of nurses in hospitals Brigjend H.Hasan Basry Kandangan.